Pengaruh Penanaman Modal Asing, Teknologi dan Jumlah Penduduk Terhadap Pertumbuhan Ekonomi di Indonesia - Tjahjono, Regita Maheswari; Yunitasari, Duwi; Santoso, Edy (Jurnal Ekonomi-Qu, 2024)
This research is motivated by the phenomenon that occurred in Indonesia regarding economic growth which from 2014-2021 experienced a drastic decline and viewership. The aim of this research is to determine the influence of foreign investment (X1), technology (X2), population (X3), and economic growth in Indonesia (Y). This type of research uses descriptive quantitative using the explanatory research method. The research location was carried out in Indonesia in 2023 by taking data from 2014-2021. The data used in this research is secondary data. Data analysis tools use Panel Data or Pooled Data. From the results of the data analysis carried out, it shows that: (1) Foreign direct investment has a significant effect on economic growth in Indonesia. (2) Technology has a significant effect on Economic Growth in Indonesia. (3) Population has a significant positive effect on Indonesia's Economic Growth.